2008
DOI: 10.1097/mnm.0b013e3282f1bbde
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glomerular filtration rate measurements with the two plasma sample and single plasma sample, gamma camera Gates, creatinine clearance, and prediction equation methods in potential kidney donors with normal renal function

Abstract: Among the SPSMs, CGmW can reflect GFR more accurately than the other methods. Neither the gamma camera Gates method nor the creatinine clearance method nor the prediction equations (Cockcroft-Gault and MDRD) could calculate GFR accurately. All these techniques could result in mistakes in the management of potential kidney donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
3
14
1
Order By: Relevance
“…However, there is also some debate whether the Gates' method is proper for determining the GFR (34,35). Aydın et al reported that the Gates' method is weakly correlated with the TPS method (36). Nevertheless, Assadi et al revealed that the Gates' method has a good correlation with the plasma sample method and was more precise than the CG method (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also some debate whether the Gates' method is proper for determining the GFR (34,35). Aydın et al reported that the Gates' method is weakly correlated with the TPS method (36). Nevertheless, Assadi et al revealed that the Gates' method has a good correlation with the plasma sample method and was more precise than the CG method (37).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Gates method, as creatinine clearance, should overestimate the true GFR, and this finding has been repeatedly reported. In particular, in a population of 115 potential kidney donors with normal renal function the Gates method overestimated GFR [20]. Moreover, a recent comparison between 99mTc-DTPA clearance using the Gates method and a two-blood sample method with MDRD and CKD-EPI, in a population of renal donor candidates and oncological patients treated with nephrotoxic chemotherapy, showed that nuclear medicine methods overestimated the GFR value in comparison to creatinine based equations [21].…”
Section: Discussionmentioning
confidence: 99%
“…Whichever protocol is used, it is imperative that the technique is meticulous and that the protocol is followed correctly [24]- [26]. Multiple blood sample techniques and subsequently single blood sample technique were developed to improve the accuracy of the computed GFR [27].…”
Section: Discussionmentioning
confidence: 99%